2023
DOI: 10.22141/2307-1257.11.4.2022.386
|View full text |Cite
|
Sign up to set email alerts
|

Executive summary of the KDIGO 2022 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease: an update based on rapidly emerging new evidence

Abstract: No abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 22 publications
1
47
0
9
Order By: Relevance
“…The two systematic reviews suggested that compared with high-salt diet, low-salt diet (with a mean difference in sodium intake of 80 mEq/day) significantly reduces SBP of 4.9 mmHg and proteinuria of 0.39 g/day and albuminuria of 0.05 g/day [27]. Taken together, these data support current international recommendations of dietary salt restriction in individuals with diabetes with or without hypertension or evidence of kidney disease [9 ▪ ,10].…”
Section: Salt-restricted Dietsupporting
confidence: 55%
See 1 more Smart Citation
“…The two systematic reviews suggested that compared with high-salt diet, low-salt diet (with a mean difference in sodium intake of 80 mEq/day) significantly reduces SBP of 4.9 mmHg and proteinuria of 0.39 g/day and albuminuria of 0.05 g/day [27]. Taken together, these data support current international recommendations of dietary salt restriction in individuals with diabetes with or without hypertension or evidence of kidney disease [9 ▪ ,10].…”
Section: Salt-restricted Dietsupporting
confidence: 55%
“…The International Society of Renal Nutrition and Metabolism advocates ‘kidney-friendly recipes’ with a ‘personalized nutrition’ care approach for patients with chronic kidney disease [7,8]. In the Kidney Disease Improving Global Outcomes (KDIGO) clinical practice guidelines, lifestyle intervention was recommended as standard management practices in blood pressure and diabetes management in patients with chronic kidney disease [9 ▪ ,10].…”
Section: Introductionmentioning
confidence: 99%
“…With the consistency of organ protective benefits across multiple large clinical trials, SGLT‐2 inhibitors should first and foremost, be considered as a standard of care for organ protection in at risk individuals with CKD and atherosclerotic heart disease regardless of diabetes status, and not just for their glucose lowering properties 22 . Indeed, various professional clinical guidelines have taken such a stance, with many recommending SGLT‐2 inhibitors as first‐line treatment in patients with type 2 diabetes mellitus and atherosclerotic heart disease, heart failure, DKD and CKD 27–30 …”
Section: Indications For Sglt‐2 Inhibitors Treatmentmentioning
confidence: 99%
“…Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are recommended as first-line therapy in patients with type 2 diabetes and CKD who have an eGFR ≥20 ml/min per 1.73 m 2 . 1,2 Although randomized controlled trials have shown the cardiovascular and renoprotective effects of SGLT2i in patients with diabetic kidney disease, 3,4 their uptake in routine clinical practice has been slow: Recent studies show that as few as 6% of patients with CKD and type 2 diabetes are currently prescribed SGLT2i in the United States. 5,6 This is especially concerning because these patients are at high risk for cardiovascular disease and kidney disease progression.…”
Section: Introductionmentioning
confidence: 99%